MAKAN BERGIZI GRATIS : STRATEGI KEBIJAKAN PUBLIK MENUJU GENERASI EMAS INDONESIA 2045 - Nango, Marselina; Purwoko, Budi; Hazim, Muffarihul; Karwanto, Karwanto (Lembaga Penelitian STKIP Widya Yuwana, 2025)
The Free Nutritious Meal Program is a government strategy to improve the quality of Indonesian human resources by fulfilling nutrition for vulnerable groups, namely pregnant women, children under five years old (Balita) and school children. From a public policy perspective, the program reflects a serious commitment of President Prabowo's government to improve Indonesian human resource, health, welfare and productivity. Economically, the program not only has a great potential to encourage the increase of productivity of Indonesian, but also presents some serious challenges such as financing and fiscal sustainability. This research was conducted using the literature review method. This method is a scientific research method where research data is obtained from various reading sources such as books, journals, scientific articles, etc. The method helps researcher to examine various previous research results which are relevant and related to the research topic being worked on. The aims of the research are to analyze so called chronic nutrition and stunting as major challenges to superior Indonesian human resource; and to criticize the program designed to respond to the chronic nutrition and stunting problem. The research results reveal the program is not only beneficial in terms of meeting the nutritional needs of vulnerable groups, but also has a close correlation of improving the quality of human resources, productivity of the Indonesian people as well as inclusive economic growth.